Two wavelength femtosecond laser induced DNA-protein crosslinking. - Russmann, C (1998)
Nucleic acid-protein interactions are essential for storage, reproduction and expression of genetic information. Biochemical methods, such as dimethyl sulfate genomic footprinting, have been developed to study stable protein-DNA interactions in vivo and chemical crosslinking has been used for less stable interactions, but the chemical agents are slow, damage cells and perturb native equilibria. To avoid these perturbations, UV laser crosslinking offers an alternative, although the energies required for significant crosslinking cause extensive DNA damage. We find that a combination of femtosecond laser pulses at two different wavelengths, in the UV and the visible range, increases the crosslinking efficiency while minimizing DNA damage. This technique also allowed us to directly measure the singlet S1lifetime of native DNA (tauS1 = 3.2 +/- 0.2 ps), which is mainly determined by the lifetime of thymine [tauS1 = 2.8 +/- 0.4 ps for (dT)16], the photochemically most reactive base. Our results suggest that two wavelength femtosecond laser pulses are well suited for the identification of transcription factors interacting with defined sequences and for studying the kinetics of protein-nucleic acid interactions in intact cells.